2011
DOI: 10.1007/s13197-011-0341-0
|View full text |Cite
|
Sign up to set email alerts
|

Positional effects on soybean seed composition during storage

Abstract: This investigation was conducted in order to determine the degree of biochemical changes during natural ageing of soybean seeds borne on different positions on stem axis. Biochemical analysis of field grown soybean seeds revealed significant differences in their oil and protein contents as a function of nodal positions. Both oil and protein content decreased after 180 days of storage (DOS) at all the nodal positions. Proportions of membrane lipids in seeds were less in basal as compared to apical positions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
1
20
0
4
Order By: Relevance
“…This is because the cotyledons are a source of stored lipids, and was deemed undesirable to study polar lipid changes and lipid peroxidation in a tissue that contained considerable quantities of nonmembrane lipids. It has long been suggested that lipid peroxidation (or autoxidation) is increased during storage (Sharma et al 2011) and is a primary cause of seed deterioration. Major peroxidation damage occurs during storage (Stewart and Bewely 1980), but only when high RH initiates imbibition process.…”
Section: Enzymes and Fatty Acid Profilementioning
confidence: 99%
“…This is because the cotyledons are a source of stored lipids, and was deemed undesirable to study polar lipid changes and lipid peroxidation in a tissue that contained considerable quantities of nonmembrane lipids. It has long been suggested that lipid peroxidation (or autoxidation) is increased during storage (Sharma et al 2011) and is a primary cause of seed deterioration. Major peroxidation damage occurs during storage (Stewart and Bewely 1980), but only when high RH initiates imbibition process.…”
Section: Enzymes and Fatty Acid Profilementioning
confidence: 99%
“…The accumulation of MDA is associated with lipid peroxidation as a result of the attack of ROS on polyunsaturated fatty acids, leading to seed deterioration and reduced viability (El-Maarouf-Bouteau, Mazuy, Corbineau, Kumar et al, 2015). The accumulation of MDA during ageing is reported in several species, including sunflower (Kibinza et al, 2006), wheat (Lehner et al, 2008), cotton (Goel et al, 2003), and soybean (Sharma et al, 2013), during artificial and natural ageing. Despite these observations, Kibinza et al (2006) also observed a reduction in MDA content in sunflower seeds stored at low moisture content and concluded that seed deterioration was not associated with lipid peroxidation under those conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) content is considered a biomarker of oxidative damage (Bailly et al, 1996) and is a commonly used method for the determination of lipid peroxidation (Cai et al, 2011); the accumulation of this compound is observed in the deterioration of lipid-rich seeds of some species, such as cotton (Goel, Goel, & Sheoran, 2003), sunflower (Kibinza, Vinel, Côme, Bailly, & Corbineau, 2006), and soybean (Sharma, Kaur, Bansal, & Gill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, oil content may influence seed longevity. According to Sharma et al (2013), soybean seeds from basal positions showed more deteriorative changes during storage than those from apical positions, which might be related to the higher lipid content in seeds from the basal portion of the soybean stem axis than in those from the apical portion. It is believed that lipid peroxidation is the main cause of seed deterioration in dry seeds during storage, which in turn influences longevity (Bewley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%